The Correlation between Motivation and Writing Skill of the Seventh-Grade Students - Aryandari, Gusti Ayu Nyoman Sukma; Agus Pramerta, I Gde Putu; Sri Widhiasih, Luh Ketut (Journal on Studies in English Language Teaching (JOSELT), 2025)
Writing is a vital learning tool that helps students better grasp language elements in authentic settings, which is why it is so important in language instruction. This implies that in order for students to write well, they must use their minds. Motivation is therefore essential in writing since it is an internal force that motivates and enables students to act. The researcher is therefore interested in determining whether motivation and writing ability are significantly correlated. The primary objective of this research is to ascertain whether there is a noteworthy correlation between the writing proficiency and motivation of seventh-grade students at SMP Negeri 14 Denpasar during the 2024–2025 academic year. Using an ex-post facto design and a correlation technique, the study included 122 students from three classes who were chosen using cluster sampling. A writing exam and a questionnaire were the research instruments used to gather data. The research process revealed a high correlation between writing skills and motivation. The findings demonstrated a considerable correlation (a Pearson correlation coefficient of 0.727) between students' writing abilities and motivation. In summary, writing proficiency and motivation are significantly correlated among seventh-grade students at SMP Negeri 14 Denpasar in the 2024–2025 school year.